Karbala as a Resistance Metaphor in Irfan Siddiqui's Poetry - Gulzar, Zaiba; Moeed, Shoiba; Tayib, Tahir Abbas (sourcecoder, 2023)
Metaphors continue to be born in every age, which are helpful in conveying and understanding the meaning along with the interpretation of their era and also bring forward the thought and vision of the poet. Karbala was a great tragedy that influenced people living all over the world with its important lessons: self-respect and self-control, and sacrifice. The peak of the trend happened in the 60s when there were new experiments in the field of symbolism and metaphors in literature. The nature of Karbala metaphor is mentioned in the poetry of Irfan Siddiqui, this journey can be divided into three stages. First: This passage in the poetry introduced some possibilities other than the description or allusions of the event which brought to mind about Karbala. Secondly, this metaphor is helpful in the form of social and contemporary consciousness or sensibility in Irfan Siddiqui's poetry. Reaching the third and last stage, they use this great tragedy to raise the voice of truth against oppression, to protest, to adopt a resistance approach instead of surrendering.